The Effect of Capital Structure, Tax Planning and Inflation on Tax Avoidance - Dinar Ambarita; Hilal Ma’aruf; Ibrahim Ibrahim (PT. Publikasiku Academic Solution, 2024)
This research aims to determine and provide empirical studies capital structure, tax planning and inflation on tax avoidance. Capital structure uses the Debt to Equity Ratio measurement, tax planning uses the Tax Retention Tare (TRR) measurement. Inflation uses the consumer price index and tax avoidance uses the cash effective tax rate. This research is a quantitative research with a research population of industrial companies listed on the Indonesia Stock Exchange for the period 2018-2022. The research population for this company was taken using a purposive sampling method to obtain 13 (thirteen) companies, so the sample obtained was 65 (sixty five) companies. The analysis technique uses Panel Data Regression Model Analysis using the statistical management program Eviews 10. The results of the research show that capital structure has an effect on tax avoidance, tax planning has a negative effect on tax avoidance and inflation has a negative effect on tax avoidance. Based on the results of the hypothesis, it shows that the variables of capital structure, tax planning and inflation simultaneously (simultaneously) have an effect on tax avoidance.